Critical Literacy in Literacy Studies as Global Research: Bibliometrics Analysis - Nouval Rumaf; Dadang S. Anshori; Vismaia S. Damaianti; Andoyo Sastromiharjo; Siti Fatihaturrahmah Al Jumroh (Universitas Muhammadiyah Malang, 2025)
This study examines critical literacy as one of the important elements of literacy research in the global digital era using a bibliometric analysis approach. The background of this study shows that literacy development not only focuses on basic skills but also extends to important aspects needed to deal with the flood of information in the multimedia era. The purpose of this article is to analyse global research on the topic of critical literacy in the field of literacy studies. This study uses a qualitative method with data-based bibliometric analysis techniques from Dimensions and Publish or Perish, which are analysed using VOSviewer. The method used in analysing Preferred Reporting Items for Systematic Reviews and Meta-Analysis. The data collected are scientific articles with the keyword Critical Literacy, which were collected from the Dimensions database on June 29, 2023, with a publication year limit of 2019–2023. The data extraction results presented in the form of the number of publications, citations, research fields, journals, and authors. Furthermore, in the VOSviewer analysis, the presentation focuses on Network visualisation for co-occurrence, Overlay visualisation for co-occurrence, Density visualisation for co-occurrence, and Network visualisation for co-authorship. So that it results in the conclusion that the topic of critical literacy in the field of literacy studies which is global research still provides opportunities for other researchers to continue to develop this research trend through online publications, by linking critical literacy with other topics such as literacy education, digital technology, digital thinking skills, and covid.